Social inclusion facet among refugee communities in refugee community settlement scheme, Kinarut, Papar, Sabah - Emmy Liew; Badariah Saibeh (Human Resource Management Academic Research Society (HRMARS), 2024)
Almost 100,000 people, mostly Muslims flee their homeland due to war between the independence-sought Moro National Liberation Front (MNLF) and the government. They were allowed to stay and work in Sabah by the ruling government. A settlement scheme was built to manage them. Documentation was provided to record their presence. Provision of fishing boats and nets, and trading equipment to help them meet end needs. In the early days, refugee children were allowed to attend national schools. Some refugees have assimilated with the locals through marriages. However, after 5 decades, they still face arrest, incarceration, and deportation. The objective of this study is to analyse the degree of social inclusion experienced by the refugees living in the Refugee Community Settlement Scheme, Kinarut, Papar, Sabah from the perspective of access and participation. This study employs a qualitative research design and engaged a purposive sampling. 39 respondents participated through administered questionnaires. Findings were analysed using the Theory of Social Inclusion by Gidley et al. (2010). Findings reveal that refugees living in the scheme experienced a degree of social inclusion of access and participation but with restriction. Notably, after 5 decades in Sabah, these refugees and their descendants are partially included. Unable to go anywhere, refusing to return to their so-called homeland, and incapable of escalating their human potential, refugees are stranded in Sabah. A holistic approach backed with strong political will, and civic awareness among the local people, together with the support of the NGOs is needed to work out refugee issues in Sabah.